Complement-targeted therapies in kidney transplantation—insights from preclinical studies - Anwar, Imran J.; DeLaura, Isabel; Ladowski, Joseph; Gao, Qimeng; Knechtle, Stuart J.; Kwun, Jean (Frontiers in Immunology, 2022)
Aberrant activation of the complement system contributes to solid-organ graft dysfunction and failure. In kidney transplantation, the complement system is implicated in the pathogenesis of antibody- and cell-mediated rejection, ischemia-reperfusion injury, and vascular injury. This has led to the evaluation of select complement inhibitors (e.g., C1 and C5 inhibitors) in clinical trials with mixed results. However, the complement system is highly complex: it is composed of more than 50 fluid-phase and surface-bound elements, including several complement-activated receptors—all potential therapeutic targets in kidney transplantation. Generation of targeted pharmaceuticals and use of gene editing tools have led to an improved understanding of the intricacies of the complement system in allo- and xeno-transplantation. This review summarizes our current knowledge of the role of the complement system as it relates to rejection in kidney transplantation, specifically reviewing evidence gained from pre-clinical models (rodent and nonhuman primate) that may potentially be translated to clinical trials.